Profile of flavonoid bioactive compounds in moringa leaves (Moringa oleifera) as phytoestrogens - Primiani, Cicilia Novi; Pujiati , Pujiati; Prayitno, Trio Ageng; Setiawan, Mohammad Arfi; Rivera, Alice Tonido (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Moringa oleifera with the local name moringa, is widely used for health, as a medicinal plant. However, its potential as a natural estrogenic is not yet known. The study aimed to analyse and identify flavonoid compounds of moringa leaves and to analyse the estrogenic potential of moringa leaves on 17β-estradiol levels of female rats. Research with an experimental approach includes: 1) Metabolite profiling of moringa leaf extract using 95% methanol solvent, with stages including extract dilution, protein precipitation, and extract purification with SPE. Extract purification using solid phase extraction using C18 Sep-Pak; 2) Induction to 4-5 months female Wistar rats, 240 - 280 g, 24 heads, grouped into 3 treatment groups, namely control (P0), administration of 17β-estradiol (P1) and administration of 1.5 ml moringa leaf feeling water (P2), treatment for 25 days. Data collection techniques include LCMS chromatogram data and data on 17β-estradiol levels taken from rat tail veins. Descriptive data analysis techniques include: 1) Chromatogram result data of flavonoid compound groups and 2) Data on 17β-estradiol levels using ELIZA on day 26. The conclusion of the results showed that the flavonoid compounds of moringa leaves were 29 compounds, including isoflavone and coumestan groups. Giving moringa leaf juice can increase 17β-estradiol levels in rats by 524.346 mg/dl.